Stratified or comprehensive? The economic efficiency of school design - Giorgio Brunello; Massimo Giannini (Fondazione Eni Enrico Mattei (FEEM), 2000)
This paper looks at the efficiency implications of differences in secondary school design. The key aspect we focus on is the degree of differentiation between vocational and general education. Using a simple model of endogenous job composition, we study the interaction between relative demand and relative supply of skills and characterise efficient school design by a government which runs schools and cares only about total net output. We show that neither a comprehensive nor a stratified system unambiguously dominates the other system for all possible values of the underlying parameters. Using numerical solutions, we show that efficiency does not necessarily require perfect sorting of graduates to jobs. We also show that government policy is not always supported by majority voting. When schools are stratified, majority voting could increase the elitist nature of general schools by rising the admission standard above efficient levels. At the same time, and depending on the values of the underlying parameters, efficient stratified schools could be voted down in favour of less efficient comprehensive schools.
Keywords: I21; 330; Allgemeinbildende Schule; Berufsbildung; Bildungsökonomik; Allokationseffizienz; Bildungschancen; Ökonomische Theorie der Demokratie; Wahlverhalten; Theorie